Modelos y funciones de dirección escolar en España: el caso de Tarragona - Barrios-Arós, Charo; Camarero-Figuerola, Marta; Tierno-García, Juana María; Iranzo-García, Pilar (Revista Iberoamericana de educación, 2015)
Different research on the professionalization of school management show the distance between the relevant legislation and the actual ability of the directors to develop some functions entrusted, such as pedagogical leadership and coordination, innovation and the ones of relationship with the community. Therefore, in our study we set out to identify, with a methodology to obtain representative data in a broad geographical context, different models of school management at public and private-funded elementary schools and contrast them with current legislation, to deepen in what leadership roles directors find more difficulties and require therefore conditions of greater support, training and collaborative work with other directors. We have worked with a sample of 128 principals of primary schools in the province of Tarragona (Spain). The results show a greater presence of management models than pedagogical leadership as well as the avoidance of actions relating to the coordination and participation of the educational community in the governance of schools. Also appear relationships between leadership, gender and experience in the job.